Some of Merleau-Ponty’s contributions to pedagogy - Manzi, Ronaldo Filho (2022)
This paper seeks to present and reflect on some contributions that the philosopher Maurice Merleau-Ponty brings to pedagogy during his courses on child psychology and pedagogy achieved in Sorbonne between 1949 and 1952. It will be highlighted how the philosopher insists that it is in the intersection of knowledge that we are forced to think otherwise. Thus, studies on psychoanalysis, anthropology, culturalism, for instance, in his view, are fundamental for pedagogical reflections. This way of thinking renews our conception of children’s world, as the children’s relation with the world, with others and with themselves. To expose this, we will first present some reflections on childhood that influenced the experience of the philosopher’s own thought. Finally, we will present one of Merleau-Ponty’s courses, “The child seen by the adult”, in which is revealed the philosopher’s originality in bringing to light some knowledge apparently distant from pedagogical reflections, but which forces us to think.